Substance use and HIV-related sexual risk behaviors in Myanmar migrant workers in Mae Sai, Chaingrai Province, Thailand - Htet Aung (Chulalongkorn University, 2013)
Thesis (M.P.H.)--Chulalongkorn University, 2012